2008
DOI: 10.1123/jsr.17.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Neural Gliding Techniques for the Treatment of Carpal Tunnel Syndrome: A Systematic Review

Abstract: Context:There are discrepancies regarding the efficacy of neural gliding exercises for the management of carpal tunnel syndrome (CTS). Objective: To conduct a systematic review assessing the efficacy of neural gliding in comparison to alternative nonsurgical treatment for the management of CTS. Evidence Acquisition: A computerized search was performed in April 2008. Criteria for inclusion required that studies (1) were written in English, (2) examined the efficacy of neural gliding techniques for treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 57 publications
(95 reference statements)
0
15
0
1
Order By: Relevance
“…An interesting point about the success of the neural mobilization in CTS is highlighted by McKeon and Yancosek [31]. In their review, they say that it is necessary to stratify subjects according to the severity of symptoms, as the neural mobilization is a nonsurgical treatment option and should be applied only to mild or moderate cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting point about the success of the neural mobilization in CTS is highlighted by McKeon and Yancosek [31]. In their review, they say that it is necessary to stratify subjects according to the severity of symptoms, as the neural mobilization is a nonsurgical treatment option and should be applied only to mild or moderate cases.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, they say that it is necessary to stratify subjects according to the severity of symptoms, as the neural mobilization is a nonsurgical treatment option and should be applied only to mild or moderate cases. Conservative treatment aims to delay or stop disease progression and subsequent surgical interventions, and thus for patients with severe CTS, surgery may be the only effective treatment option for relieving compression of the median nerve and reducing progression of the disease [31]. This assertion finds support in Oskay et al [27] which followed this guidance and included in the rehabilitation program only mild or moderate cases.…”
Section: Discussionmentioning
confidence: 99%
“…Existen distintos tratamientos enfocados a disminuir la sintomatología e incrementar la funcionalidad en pacientes que presentan STC, en los cuales se encuentran las técnicas de neurodinamia (29)(30). Esta intervención corresponde a una técnica de terapia manual, en la que las fuerzas están dirigidas a las estructuras neurales mediante el posicionamiento y el movimiento de múltiples articulaciones para descomprimir la zona, liberando la presión del nervio afectado (29).…”
Section: Descripción De La Intervenciónunclassified
“…7 Some studies have shown that neurodynamic interventions exhibit promising results for decreasing pain in CTS [8][9][10] ; however, a review focused on neural mobilization for CTS concluded that the evidence for the effects of nerve gliding neurodynamic exercises is not clear. 11 The authors of this review concluded that the neurodynamic techniques may be effective in a specific population of subjects with CTS, particularly in those with lower hyperexcitability of the central nervous system. 11 This hypothesis was partially supported by a study where central sensitization was not present in women with CTS who are likely to achieve a successful outcome with physical therapy including soft tissue mobilization and a passive nerve slider neurodynamic technique targeted to the median nerve.…”
mentioning
confidence: 96%
“…11 The authors of this review concluded that the neurodynamic techniques may be effective in a specific population of subjects with CTS, particularly in those with lower hyperexcitability of the central nervous system. 11 This hypothesis was partially supported by a study where central sensitization was not present in women with CTS who are likely to achieve a successful outcome with physical therapy including soft tissue mobilization and a passive nerve slider neurodynamic technique targeted to the median nerve. 12 The purpose of this case series was to examine possible effects of a nerve slider neurodynamic intervention targeted to the median nerve on widespread pressure pain sensitivity in individuals with CTS.…”
mentioning
confidence: 96%